Creation of e-Poster of The God of Small Things by the Students: Applied Method of Teaching Practice of Gender Issue - Suci Suryani; Nurul Lailatul Hasanah; Imron Wakhid Harits; Pavlina Hanakova (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: The study focuses on teaching students about the power of dualism that contributes to the oppression of women and the exploitation of nature. Method: Descriptive qualitative research is used in this study. Results: The results of this study teach students that the oppression experienced by female characters is caused by the power of dualism, such as civilized/primitive, male/female, and subject/object dualism, which places women in a lower position. Meanwhile, the power of human/nature and reason/nature dualism is the cause of the exploitation of nature. Novelty: The analysis of dualism has been done in some previous studies, but there are several powers of dualism in this study that previous studies have not found. The power of civilized/primitive, subject/object, and reason/nature dualism are new dualisms in this study. In addition, this study teaches students about the power of dualism in gender inequality and environmental exploitation in the novel, which also occurs in real life.